The business of film a practical introduction - Landry, Paula; Greenwald, Stephen R. (Routledge, 2018)
The updated second edition of this text introduces readers to the business of film at every stage of the filmmaking lifecycle, from planning and production to distribution. Authors Paula Landry and Stephen R. Greenwald offer a practical, hands-on guide to the business aspects of this evolving industry, exploring development, financing, regional/global/online distribution, business models, exhibition, multi-platform delivery, marketing, film festivals, production incentives, VR/AR, accounting, and more. The book is illustrated throughout with sample financing scenarios andcharts/graphics, and includes detailed case studies from projects of different budgets and markets.This new and expanded edition has further been updated to reflect the contemporary media landscape, including analysis on major new players and platforms like Netflix, Amazon, Google and Vimeo, shifting trends due to convergence and disruption from new technology, as well as the rise of independent distribution and emergent mobile and online formats. An eResource also includes downloadable forms and templates, PowerPoint slides, quizzes and test banks, and other additional resources.
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher
Keywords: Motion picture industry; Motion picture industry -- United States; Cinéma; Industrie; Cinéma; Industrie; États-Unis; PERFORMING ARTS / Reference; United States